The Correlation Between Students' Critical Thinking and Argumentative Skill in IAIN Bukittinggi - Lia Aulia Suryani; Hilma Pami Putry; Hafizul Khair (Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This research was directed to find out whether there any significant correlation between students' critical thinking and argumentative writing skill in IAIN Bukittinggi. The researcher found several problems in the field, the problems were students got difficulties in starting and developing their ideas into writing a paragraph, they have limited vocabulary in the English language, and some of the students don’t use transition signals. This research employed a correlation design. The population of this research was the students of the fifth semester in Iain Bukittinggi. The researcher used random sampling were the students of class 5A, class 5B, and 5C to get the sample of the research. In collecting the data, the researcher used a reading test to know of students of critical thinking, and the researcher used of writing test to know of argumentative writing essay. The data were processed and analyzed by SPSS 22.0 Statistic technique of product-moment t-test formula and consulted the result into t-table with the level of significant α = 0.05.The result of this study by the correlation coefficient (r-x-y) 0,787. It shows that there was a high correlation between students' critical thinking and argumentative writing, it included the scale of r interpretation score between 0,60- 0,79. Furthermore, with df =25. And the level of significance 0,05 (α= 5%) obtained 0,396. So , try = 0,787 > t table 0,396. So, Ha was accepted and Ho was rejected. It means that there was a correlation between students critical thinking and argumentative writing skill.